Advancements in diffusion bonding of aluminium and its alloys: a comprehensive review of similar and dissimilar joints. Issue 4 (2nd October 2022) - Lathashankar, B.; Tejaswini, G. C.; Suresh, R.; Swamy, N. H. S.
ABSTRACT: Diffusion bonding (DB) is a novel joining process exploiting diffusion of atoms on faying surfaces when appropriate values of governing parameters such as temperature, pressure and bonding time are applied. In particular, DB of aluminium alloys is well investigated in literature owing to lot many advantages of using Al alloys in engineering applications and challenges due to the formation of oxide films in forming sound joints. This paper elaborately reviews the advances made in the Al and its alloys, focusing on interface morphology, interlayer role, parameters influencing the joining process, their optimisation, modelling and monitoring of the process, etc. At the end, future directions for potential research are also presented.